Short Term Performance Persistence of Open Ended Equity Funds: Indian Evidence - Rama Krishna, Y. (Indian Journal of Finance, 2012)
This study examines the short-term performance persistence of select Indian Equity (growth) mutual funds during the period 2008 and 2011. First, to assess the performance of sample funds, the author uses return variance analysis. Second, he uses Sharpe’s index to rank the funds. Finally, to test the short term performance, the researcher pursues the Brown&Goetzmann (1995) and Malkiel’s (1995) measures. Majority of the sample funds report results similar to the Proxy for the market. These funds move in tandem with the market. The study reports non existence of short term performance. The study concludes that mutual fund managers need to change their fund management style.